Developing Biology Learning Tool in Senior High School By Using Problem Solving Method to Students’ Learning Outcome and Their Critical Thinking Skill - Nurul Azizah; Aminuddin Prahatama Putra (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
This research aimed at developing learning tool for Biology subject by using problem solving method to students’ learning outcomes and critical thinking skills on the material Human Digestive System, based on the feasibility of the study, the feasibility of teaching and learning activities, the learning outcome and critical thinking skills of students. This was a research and development study (R & D) with ASSURE development model. The series of this learning tool development were: (1) the establishment of model development, (2) the development of procedure, (3) product testing, and (4) field testing. The small group sample was students of XI IPA 2 and for field testing was students of XI IPA 1 SMAN 1 Sungai Loban Year 2014/2015. The type of data required in the research and development were data from the feasibility of the study, the feasibility of lesson plans, the implementation of lesson plans, learning outcomes, critical thinking skills, and students’ response. The data validation analysis of learning tool, the implementation of lesson plans and students’ activities were quantitatively measured by using category 1 (not enough/incomplete), 2 (adequate/enough), 3 (good), 4 (very good). The validation results of learning tool development showed that the device got 3 score in good category and adequate for use. The implementation of learningtocritical thinkingskillcan improve theability to createquestions, formulate hypotheses,and draw conclusionswith an averageof 1.00N-Gain, andthe abilityto analyzedatawith an averageN-Gain 0.67.The students wereable to completeallthe learningindicatorswithindividualandclassicalcompleteness by96.7% in the posttest. Based on the analysis of data, it can be concluded that learning Biology with problem solving method which had been implemented is effective to achieve learning mastery and critical thinking skill ability of the learners.Keywords:Problem Solving, Learning Outcome and Critical Thinking